Adiponectin and leptin gene variants and their effects on body weight trajectories in children from birth to 6 years of age: the PREDI Study - Kroll, Caroline; Farias, Dayana Rodrigues; Kac, Gilberto; de França, Paulo Henrique Condeixa; Mastroeni, Marco Fabio (British journal of nutrition, 2021)
Excess body weight confers a high risk to human health. Body weight variation between subjects can be partially explained by genetic differences. The aim of the present study was to investigate the association of genetic variants in the ADIPOQ (rs2241766) and LEP (rs7799039) genes with body weight trajectories in children from birth to 6 years of age. This was a prospective cohort (PREDI Study). Socio-economic, biological and anthropometric data were collected at four time points: at birth in the maternity unit; 1–2, 4–5 and 6 years old at the participants’ homes. Genotyping was performed by PCR-restriction fragment length polymorphism. Poisson regression and linear mixed-effect regression models were used to address the association of ADIPOQ and LEP genotypes with BMI. Excessive body weight at pre-pregnancy (β = 0·339, P = 0·01) and excessive gestational weight gain (β = 0·51, P < 0·001) were associated with children’s BMI trajectory from birth to 6 years. The ADIPOQ-rs2241766 TG or GG genotype was associated with a higher risk of excess body weight in the first 6 years of life (both sexes relative risk 1·25, 95 % CI 1·01, 1·56; female relative risk 1·67, 95 % CI 1·20, 2·31). BMI increased over the years according to the presence of the TG or GG genotype (β = 0·01, 95 % CI 0·01, 0·02), particularly in females (β = 0·02, 95 % CI 0·01, 0·04). The ADIPOQ-rs2241766 TG and GG genotypes increased the risk of excess body weight in children from birth to 6 years of age and had a positive effect on body weight trajectories in girls. The LEP-rs7799039 genetic variant was not associated with body weight trajectory in children.